The Role of English Proficiency in Supporting Academic Achievement and Career Opportunities of University Students - Muhammad Farras Fadhil; Elsa Septiana; Oni Sawitri; Riza Abdillah; Wandi Syahfutra; Novela Nurafrezah (Widya Accarya, 2025)
This study aims to explore the role of English proficiency in supporting academic careers, with a particular focus on students at the University of Muhammadiyah Riau. As English is a global language crucial for academic and professional success, this study examines its impact on students' academic performance and career opportunities. The research employs a quantitative approach using a questionnaire to assess students' English proficiency and its relationship with their academic success. The data analysis technique uses in this research is correlation analysis with the Corrected Item-Total correlation formula. The results of research on 20 student respondents showed a strong positive correlation between English proficiency and academic achievement, particularly in reading and writing skills, which were linked to higher GPAs and active participation in academic activities. However, lower speaking proficiency indicates a need for further development in oral communication skills. This study underscores the importance of English proficiency for academic success and career advancement, suggesting that enhancing students' speaking abilities could improve their overall academic and professional outcomes. Further research with a larger sample size is recommended to enhance the generalizability of these findings.